Innovation Rumen Microbial Degradation of a Selection Oilseeds in a Consecutive Batch Culture System In vitro - Ismartoyo (Research Perspectives of Microbiology and Biotechnology Vol. 5, 2024)
An experiment was conducted to examine the rumen microbial degradation of whole cottonseed (WCS) compared to other tropical oilseeds in a consecutive batch culture (CBC) system. The selection of oilseeds was mustard seed (cv. Albatross), linseed (cv. Antares) and three cultivars of rape seeds namely cv. Bienvenu, cv. Libravo and cv. Samourai. The CBC system was established according to the methods of Theodorou [1]. The results of this experiment indicated that the mean dry matter (DM) losses, gas production, and total volatile fatty acids (VFA) of WCS were significantly lower than those of other oilseeds. In contrast, mustard seed had the highest DM losses indicating that mustard seed was more readily fermentable to rumen microbes than other oilseeds. Rumen microbes appeared to adapt to the presence of oilseeds. WCS consistently had lower DM losses, gas production, and total VFA. It was concluded that the lower microbial degradation and fermentation of WCS was probably due to gossypol, tannin, and other factors such as lignin, fat, and the physical structure of fibre in WCS.